High anesthetic exposure leads to oxidative damage and gene expression changes in physicians during medical residency: a cohort study - Aun, Aline G. [UNESP]; Damasceno, Débora C. [UNESP]; Sinzato, Yuri K. [UNESP]; Nogueira, Flávia R. [UNESP]; Souza, Kátina M. [UNESP]; Lawi, Youssef S.A. [UNESP]; Guedes, Júlia L. [UNESP]; Silva, Mariane A.P. [UNESP]; de Carvalho, Lídia R. [UNESP]; Braz, Leandro Gobbo [UNESP]; Braz, Mariana Gobbo [UNESP] (Springer Nature, 2023)
Evaluation of the possible toxic effects of occupational exposure to anesthetics is of great importance, and the literature is limited in assessing the possible association between occupational exposure to anesthetics and oxidative stress and genetic damage. To contribute to the gap of knowledge in relation to cause-effect, this cohort study was the first to monitor exposure assessment and to evaluate oxidative stress, DNA damage, and gene expression (OGG1, NRF2, HO-1, and TP53) in young adult physicians occupationally exposed to the most modern halogenated anesthetics (currently the commonly used inhalational anesthetics worldwide) in addition to nitrous oxide gas during the medical residency period. Therefore, the physicians were evaluated before the beginning of the medical residency (before the exposure to anesthetics-baseline), during (1 1/2 year) and at the end (2 1/2 years) of the medical residency. Anesthetic air monitoring was performed in operating rooms without adequate ventilation/scavenging systems, and biological samples were analyzed for lipid peroxidation, protein carbonyl content, primary and oxidative DNA damage, antioxidant enzymes and plasma antioxidant capacity, and expression of some key genes. The results showed induction of lipid peroxidation, DNA damage, glutathione peroxidase activity, and NRF2 and OGG1 expression up to the end of medical residency. Plasma antioxidant capacity progressively increased throughout medical residency; oxidative DNA damage levels started to increase during medical residency and were higher at the end of residency than at baseline. Protein carbonyls increased during but not at the end of medical residency compared to baseline. The antioxidant enzyme superoxide dismutase activity remained lower than baseline during and at the end of medical residency, and HO-1 (related to antioxidant defense) expression was downregulated at the end of medical residency. Additionally, anesthetic concentrations were above international recommendations. In conclusion, high concentrations of anesthetic in the workplace induce oxidative stress, gene expression modulation, and genotoxicity in physicians during their specialization period.
Keywords: DNA damage; Gene expression; Inhalation anesthetics; Medical residency; Occupational exposure; Oxidative stress